Reduction of medication errors related to sliding scale insulin by the introduction of a standardized order sheet. Issue 3 (7th December 2016) - Harada, Saki; Suzuki, Akio; Nishida, Shohei; Kobayashi, Ryo; Tamai, Sayuri; Kumada, Keisuke; Murakami, Nobuo; Itoh, Yoshinori
Abstract: Insulin is frequently used for glycemic control. Medication errors related to insulin are a common problem for medical institutions. Here, we prepared a standardized sliding scale insulin (SSI) order sheet and assessed the effect of its introduction. Observations before and after the introduction of the standardized SSI template were conducted at Gifu University Hospital. The incidence of medication errors, hyperglycemia, and hypoglycemia related to SSI were obtained from the electronic medical records. The introduction of the standardized SSI order sheet significantly reduced the incidence of medication errors related to SSI compared with that prior to its introduction (12/165 [7.3%] vs 4/159 [2.1%], P  = .048). However, the incidence of hyperglycemia (≥250 mg/dL) and hypoglycemia (≤50 mg/dL) in patients who received SSI was not significantly different between the 2 groups. The introduction of the standardized SSI order sheet reduced the incidence of medication errors related to SSI.